A Rapid-Response Humoral Vaccine Platform Exploiting Pre-Existing Non-Cognate Populations of Anti-Vaccine or Anti-Viral CD4+ T Helper Cells to Confirm B Cell Activation. - Thomas Hills; Phillip G Jakeman; Robert C Carlisle; Paul Klenerman; Leonard W Seymour; Ryan Cawood (PLoS ONE)
The need for CD4+ T cell responses to arise de novo following vaccination can limit the speed of B cell responses. Populations of pre-existing vaccine-induced or anti-viral CD4+ T cells recognising distinct antigens could be exploited to overcome this limitation. We hypothesise that liposomal vaccine particles encapsulating epitopes that are recognised, after processing and B cell MHCII presentation, by pre-existing CD4+ T cells will exploit this pre-existing T cell help and result in improved antibody responses to distinct target antigens displayed on the particle surface. Liposomal vaccine particles were engineered to display the malaria circumsporozoite (CSP) antigen on their surface, with helper CD4+ epitopes from distinct vaccine or viral antigens contained within the particle core, ensuring the B cell response is raised but focused against CSP. In vivo vaccination studies were then conducted in C57Bl/6 mice as models of either vaccine-induced pre-existing CD4+ T cell immunity (using ovalbumin-OVA) or virus-induced pre-existing CD4+ T cell immunity (murine cytomegalovirus-MCMV). Following the establishment of pre-existing by vaccination (OVA in the adjuvant TiterMax® Gold) or infection with MCMV, mice were administered CSP-coated liposomal vaccines containing the relevant OVA or MCMV core CD4+ T cell epitopes. In mice with pre-existing anti-OVA CD4+ T cell immunity, these vaccine particles elicited rapid, high-titre, isotype-switched CSP-specific antibody responses-consistent with the involvement of anti-OVA T helper cells in confirming activation of anti-CSP B cells. Responses were further improved by entrapping TLR9 agonists, combining humoral vaccination signals 'one', 'two' and 'three' within one particle. Herpes viruses can establish chronic infection and elicit significant, persistent cellular immune responses. We then demonstrate that this principle can be extended to re-purpose pre-existing anti-MCMV immunity to enhance anti-CSP vaccine responses-the first description of a strategy to specifically exploit anti-cytomegalovirus immunity to augment vaccination against a target antigen.